The artist's guide to drawing people : 600 reference images for body movements, facial expressions, and hands - Lamérand, Jean-Pierre; Cours, Gilles (Rocky Nook, 2022)
An essential guide for all artists with more than 600 images to show readers how to draw realistic characters with examples of movement, faces, and hands. Anatomy charts and rules of proportion will also allow users to accurately represent any human subject. Including instructions for a variety of drawing techniques (graphite pencils, colored pencils, felt tip pens, etc.) and a diverse array of models, this is the ultimate guide to mastering drawing the human form.